Influence of extracorporeal membrane oxygenation on serum microRNA expression. Issue 12 (December 2019) - Scettri, M.; Seeba, H.; Staudacher, D. L.; Robinson, S.; Stallmann, D.; Heger, L. A.; Grundmann, S.; Duerschmied, D.; Bode, C.; Wengenmayer, T.; Ahrens, I.; Hortmann, M.
Objective: To date, no biomarkers have been established to predict haematological complications and outcomes of extracorporeal membrane oxygenation (ECMO). The aim of this study was to investigate the expression of a panel of microRNAs (miRNAs), which are promising biomarkers in many clinical fields, in patients before and after initiating ECMO. Methods: Serum miRNA levels from 14 patients hospitalized for acute respiratory failure and supported with ECMO in our medical intensive care unit were analysed before and 24 hours after ECMO. In total, 179 serum-enriched miRNAs were profiled by using a real-time PCR panel. For validation, differentially expressed miRNAs were individually quantified with conventional real-time quantitative PCR at 0, 24, and 72 hours. Results: Under ECMO support, platelet count significantly decreased by 65 × 10 3 /µL (25th percentile = 154.3 × 10 3 /µL; 75th percentile = 33 × 10 3 /µL). Expression of the 179 miRNAs investigated in this study did not change significantly throughout the observational period. Conclusions: According to our data, the expression of serum miRNAs was not altered by ECMO therapy itself. We conclude that ECMO does not limit the application of miRNAs as specific clinical biomarkers for the patients' underlying disease.